FAKTOR - FAKTOR YANG MEMPENGARUHI KEINGINAN MASYARAKAT AWAM MENJADI BYSTANDER CPR : Literature Review - Siti Hidayatun Nazza Darmansyah, (2020)
Bystander is a person at the scene who volunteered to help a victim of cardiac arrest. With this assistance, it can reduce the morbidity and mortality rate of cardiac arrest victims discharged from out the hospital. The purpose of the writing is to review the existing research in determining the best quality evidence related to the factors that influence the willingness of the lay community to be a bystander CPR. The method used in this research is Literature Review. The Literature search process uses three databases namely Pubmed, Science Direct, Jstore and one search engine, Google Scholar. From the extraction process seven journals that match the inclusion recommendations are included. Three themes that consist of ten factors extracted from these seven journals, which are related to the factors that affect the willingness of lay person to become bystander CPR. The first theme is the Internal Factors that include in knowledge, self confidence, and self readiness. The second is the external factor, which consist of CPR training history, training methods, and location of AED (Automated External Defibrillator) is available. The final theme is a demographic factors a which includes age, gender, education and economic status. Conclusion: CPR training history, age and gender are the factors that most influence the layperson in providing CPR. However, the knowledge, AED location, education and economic status can be prevention factors when those are absent or minor . Keywords : Bystander CPR, Willingness, A layperson